1994
DOI: 10.2214/ajr.163.6.7992723
|View full text |Cite
|
Sign up to set email alerts
|

Detection of pooled secretions above endotracheal-tube cuffs: value of plain radiographs in sheep cadavers and patients.

Abstract: OBJECTIVE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 14 publications
1
19
0
4
Order By: Relevance
“…In addition, the presence of endotracheal tubes eliminates the cough reflex and contributes to the pooling of secretions above inflated endotracheal tube cuffs. Studies have shown that pooled secretions above inflated cuffs can predispose ventilated patients to VAP because of lower airway aspiration of these contaminated secretions (Greene et al, 1994;Oikkonen and Aromaa, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the presence of endotracheal tubes eliminates the cough reflex and contributes to the pooling of secretions above inflated endotracheal tube cuffs. Studies have shown that pooled secretions above inflated cuffs can predispose ventilated patients to VAP because of lower airway aspiration of these contaminated secretions (Greene et al, 1994;Oikkonen and Aromaa, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Similarly, our study found that it was less possible to clear secretions visibly if only a few secretions existed above the cuff. The subglottic secretions produced within 24 h were estimated to be 7.8 Ϯ 1.1 mL, according to Greene et al 18 ; thus, it is more reasonable to utilize the rapid flow expulsion maneuver intermittently (eg, every 6 -8 h). The actual frequency depends on the quantity of patients' oral secretions.…”
Section: Frequency Of the Maneuvermentioning
confidence: 99%
“…Radiographic studies have revealed that secretions generally accumulate above the cuff of endotracheal tubes (in the subglottic region) before descending to the lower respiratory tract. 9 Because translocation of these secretions into the pulmonary parenchyma may lead to VAP, SSD has been used in clinical settings to combat VAP. However, SSD may also be associated with risks such as airway mucosal injury and bleeding, detection of which requires testing for occult blood.…”
Section: Zunjia Wen Is a Registered Nurse Haiying Zhang Is An Associmentioning
confidence: 99%